The Reader’s journey: navigating national development through the lens of literacy (2025)
There are some 13 countries in the world where the adult literacy rate is 100%. In Africa, the three leading countries in terms of the adult literacy rates are Seychelles (95.9%), Equatorial Guinea (95.3%) and South Africa (95%), respectively. On the other hand, Nigeria is ranked 36th out of the 54 countries of Africa with a low adult literacy rate of 62%, comprising 71.3% for Male and 52.7% for Female in 2018. Moreover, about 18.3 million children in Nigeria are out of school, with 10.2 million of primary school age and another 8.1 million of junior secondary school age. This number represents one in every five of the world's out-of-school children, making the country home to the largest number of out-of-school children globally. The literacy index in Nigeria is poor in spite of the fact that the National Policy on Education (2013) clearly stipulates that Basic Education, the education given to children aged 0 to 15 years, shall be compulsory, tuition-free, universal and qualitative. The low literacy rate in Nigeria has adversely affected the Gross Domestic Product per capita and the Human Development Index. By prioritizing literacy, which can be acquired through formal education, informal education and self-directed learning, including personal reading and exploration, and addressing the challenges that limit access to education, the full potential of individuals can be unlocked, and thereby promote sustainable development and growth. The ways University Libraries can promote Information Seeking Behaviour are outlined in this paper.